Operando X-ray radiography of liquid water distribution in 100 mm polymer electrolyte fuel cell channels - Akihiko Kato; Satoshi Yamaguchi; Wataru Yoshimune; Kazuhisa Isegawa; Masashi Maeda; Daisuke Hayashi; Takahisa Suzuki; Satoru Kato (Electrochemistry Communications, 2024)
Preventing the accumulation of water in the gas diffusion layer (GDL) proves effective in enhancing the performance of polymer electrolyte fuel cells (PEFCs). To understand the water transport phenomena in GDLs and channels of PEFCs, cell hardware for operando synchrotron X-ray radiography was developed with a 100 mm channel length, facilitating the separate quantification of liquid water in the cathode and anode GDLs. The presence of liquid water in the cathode and anode GDLs was confirmed during operation with a supply of dry gas in a counter-flow configuration. Furthermore, the amount of liquid water in the cathode and anode GDLs increased toward the cathode inlet, while the amount of water in the cathode and anode channel regions increased toward each outlet. The liquid water distribution in the GDLs along the channel direction can be attributed to water transport from cathode to anode (back-diffusion), decreasing toward the anode outlet. Therefore, conducting radiography experiments aligned parallel to the GDLs and perpendicular to the channel could provide valuable insights for a more comprehensive understanding of water transport in cells.